Igdlukúnguaq nickeliferous pyrrhotite. Texture and composition. A contribution to the genesis of the ore type - Pauly, Hans (Meddelelser om Grønland, 1958)
Because of the very remarkable phases and structures it contains, the only nickeliferous pyrrhotite so far known in Greenland is given a very thorough ore-microscopic description. The locality where this block of ore- about 28 tons-was found by STEENSTRUP in 1872 is situated on the Northeast coast of the island of Disko, which in turn lies off the West coast of Greenland. The ore was contained within a dike rock belonging to the basalt complex which i. a. forms the main part of Disko and the neighbouring regions of the Greenlandic coast. The ore itself, although it has the composition of normal nickeliferous pyrrhotite rich in nickel, presents a remarkable variety of phases and exsolution structures. It is the author’s belief that these components form an almost unbroken chain of evidence covering the whole range, from the first consolidated sulphides to exsolution phenomena representing temperatures of under 200° C. The following exsolutions were found in the ore:- 1. Chalcopentlandite, i. e. a pentlandite containing about 10 per cent. of chalcopyrite. Formed at near 850° C. 2. Chalcopyrite in rectilinear lamellae following (hoho), formed at around 700° C. 2 a. Chalcopyrite in rectilinear lamellae along (hohl), formed at around 700° C. 2b. Chalcopyrite in rectilinear lamellae following (hohl1), likewise formed at near 700°. Chalcopyrite in flame-like lamellae corresponding to about 550° C. 3 a. Chalcopyrite in flame-like lamellae of another type. 4. Pentlandite sparks formed at near 550 C. 5. Pentlandite flames of the well-known type formed at 310 °C. 6. Pyrrhotite α-β lamellae formed at around 140°C. The study of the compact ore showed that development of the ore comprised three stages: 6. An initial stage, from which the primary oxides came as a result of gases originally held within the molten sulphide mass. The main stage, where consolidation of the sulphides took place together with the solidification of oxidic material. The third stage was dominated by processes of hydrothermal character. The formation of both sulphidic and oxidic phases took place widely at the expense of earlier-formed compounds. The wealth of new observations which the author was able to make during his work on the Greenlandic ore is described in detail, after brief mention of historical data, in pages 27-65. Chemical analyses of rocks and ore will be found on pages 21 and 25. On page 65 is a list showing the mineral content of the ore. The following pages, 66 to 101, contain a discussion of the microscopic observations; the second half of that discussion deals especially with the significance of the gases originally held within the sulphide mass. Water and carbon dioxide seem to have played an important role in the forming of the ore, not as carriers of the ore material but as participants in the chemical reactions. Comparison of Canadian, African, Scandinavian and Australian occurrences with several new observations made by the author is followed by a chapter devoted mainly to summing up and placing the nickeliferous pyrrhotite in relation to other geological phenomena. The last pages contain a brief discussion of a possible relation between nickeliferous pyrrhotite and the well-known occurrence of native iron in the Greenlandic plateau basalts.